Analisis yang Berpengaruh Terhadap Penggunaan Informasi Akuntansi pada UMKM di Kecamatan Sayung - Oktavie Fresiliasari (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This research seeks to empirically evaluate the influence of business scale, education, business age, and accounting training on the application of accounting information in Sayung District. Employing a quantitative methodology, the study utilizes WarpPLS version 7.0 for data analysis, with a sample comprising 35 respondents. The dependent variable identified in this research is the Use of Accounting Information, while the independent variables include Business Scale, Education, Business Age, and Accounting Training. The results indicate that neither business scale nor education significantly affects the use of accounting information. Conversely, business age and accounting training demonstrate a notable impact on this utilization. In summary, it is crucial for MSME stakeholders to take into account the educational qualifications of MSME owners or managers, as their educational level can influence the effective application of accounting information, which is vital for business development. Additionally, to steer MSMEs towards improved practices, it is essential for these enterprises to enhance their accounting processes through the implementation of an accounting information system. This system encompasses various elements, including decision-making and operational functions. Consequently, MSMEs that effectively leverage accounting information can promote their business growth, which ultimately benefits the government, as increased MSME revenues are linked to higher state income through tax contributions.